Sri Cempaka Ayu Enterprise / Ilda Izanie Ahmad... [et al.] - Ahmad, Ilda Izanie; Abdul Rahim, Maryati; Zulkifly, Mastura; Aripin, Hasliza (2000)
Sri Chempaka Ayu Enterprise is a company that offer health and beauty care to their customer. they provide traditional treatment such as ‘jamu’, traditional massage and herbs steam bath. The company is located at Alor Setar, Kedah.